The influence of motivation and work environment on employee performance in the national unity and political agency of Bandar Lampung City - Armalia Reny Madrie WA; Eva Desriyantika; Hasbullah Hasbullah; M. Renandi ET; Susi Indrianni (Global Academy of Multidisciplinary Studies, 2024)
Purpose: This study aims to analyze the influence of work motivation and work environment on employee performance within the National Unity and Political Agency of Bandar Lampung City. Research Methodology: The research employed a quantitative method with a survey approach. The population consisted of civil servants in the agency, and a proportional sampling technique was used to select respondents. Data were collected through questionnaires and analyzed using multiple linear regression supported by validity, reliability, t-test, F-test, and coefficient of determination to test the hypotheses. Results: The findings demonstrate that both motivation and work environment significantly affect employee performance, both partially and simultaneously. Motivation contributes to performance through encouragement, recognition, and goal achievement, while the work environment influences performance through adequate facilities, interpersonal relations, and organizational climate. The combined effect shows a strong explanatory power for employee performance. Conclusions: Employee performance at the agency can be improved through strengthening motivational factors and creating a supportive work environment. Limitations: This study only examined two independent variables motivation and work environment while other potential factors such as leadership, organizational culture, and job satisfaction were not included. Contribution: Practically, this study provides input for local government institutions to improve performance management strategies. Theoretically, it enriches human resource management literature, especially in public sector organizations in Indonesia.